Consequences of “No child left behind act” pressure: the USA experience for Ukrainian educators - Andriushyna, О. (Continuing Professional Education: Theory and Practice, 2019)
The article presents desirable and unpredictable consequences of implementation No Child Left Behind Act (2001, USA) for monitoring quality of general education. NCLB Act pressure on a state, school district, school and students are investigated. The ways of using the results of monitoring quality of general education in the USA are shown. Possible consequences of monitoring realization - positive and negative, state foundation of such monitoring and its effectiveness are analyzed. The consequences of keeping the high academic standards and students educational progress are searched. The aspects of the educational monitoring that should be taken into account and analyzed for practical application in Ukraine are presented.